2016
DOI: 10.4328/jcam.3810
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Caries with the Perspective of Pediatrician

Abstract: ÖzetAmaç: Erken süt çocuğu diş çürüğü 24-72 ay çocuklarda en az bir ya da daha fazla diş çürüğü, süt dişlerinde kayıp ya da dolgu olması olarak tanımlanmak-tadır. Etyolojik faktörlerin değişim göstermesi nedeniyle erken süt çocuğu diş çürüklerinin prevalansı tüm dünyada farklılık göstermektedir. Bu çalışmanın amacı Türkiye'nin güneydoğu Anadolu bölgesinde erken süt çocuğu diş çürü-ğü prevalansını ve etyolojik faktörlerini belirlemek ve pediatrist bakışı açısı ile değerlendirmektir. Gereç ve Yöntem: Pediatri po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…More appropriate protein intake might be need for patient with ECC. As reported by previous study that multivitamin usage and tooth decay relation is not a widely questioned phenomena in ECC [22]. Our finding might be valuable for the strategy to prevent ECC focusing on S mutans serotype c and the role of specific IgA against this S mutans saliva.…”
Section: Number Of Caries Subjecs Dmftsupporting
confidence: 75%
See 1 more Smart Citation
“…More appropriate protein intake might be need for patient with ECC. As reported by previous study that multivitamin usage and tooth decay relation is not a widely questioned phenomena in ECC [22]. Our finding might be valuable for the strategy to prevent ECC focusing on S mutans serotype c and the role of specific IgA against this S mutans saliva.…”
Section: Number Of Caries Subjecs Dmftsupporting
confidence: 75%
“…In ECC patients, S mutans serotype e may be more immunogenic than serotype c and higher salivary viscosity may be due to its high protein contain as well as IgA content. score, the lower IgA anti-S mutans Decreased IgA levels, sk factor in patients re appropriate protein intake might be As reported by previous study that multivitamin usage and tooth decay relation is not a widely questioned phenomena in ECC [22]. Our finding might be valuable for the strategy to prevent ECC by serotype c and the role of S mutans serotype in serotype e may be more immunogenic than serotype c and higher salivary viscosity may be due to its high protein Part of this study was supported by Universitas Indonesia PUPT grant provided by The Ministry of Research and Technology and Higher he Republic of Indonesia 2016.…”
Section: Resultsmentioning
confidence: 80%
“…ECC has a number of causes and develops as a reaction to a combination of various socio-demographic and behavioural factors [8]. Some studies have shown an association of low vitamin D levels and dental caries in children, while others have not shown any correlation or the association [4,5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. There is clinical evidence of the association of vitamin D deficiency with dental caries in the primary dentition among Canadian populations; they are at risk of vitamin D deficiency due to high latitude geographical location [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the molecular basis of vitamin D and vitamin D receptor (VDR) have concluded that vitamin D influences tooth germ formation; it contributes to the regulation of enamel and dentine formation and maturation, and controls the stages of tooth crown development [22]. In addition, vitamin induces the formation of certain antimicrobial peptides (AMPs) such as defensins and cathelicidins, which are relevant elements in breaking the membrane integrity of the oral bacteria [15,22,23]. Salivary antimicrobial peptides concentrations showed large differences between individuals, with a significantly higher level of salivary defences in cariesfree children.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, second-hand smoke brings harm to children's general heath, including dental health. It is suggested that the exposure to second-hand smoke at home increases the risk of caries among children [12,15], but some studies found no association [16,17]. Moreover, obesity and caries are health problems that exist concurrently, mostly due to their common risk factors, including consumption of food high in calories, increased stress, and low socioeconomic status [18].…”
Section: Introductionmentioning
confidence: 99%